Soursop Leaves Extract Combined with Eucalyptus Oil: A Natural Strategy for Controlling Bed Bugs - Firman Jaelani; Dita Pratiwi Kusuma Wardani; Isna Hikmawati; Atika Nur Azizah; Ikhsan Mujahid; Muhammad Luthfi Almanfaluthi; Oei Stefani Yuanita Widodo (Jurnal Veteriner, 2025)
Insecticides used in controlling Bed bugs (Cimex lectularius)  often result in side effects and the development of resistance. Betel leaf (Piper betle Linn.), soursop leaf (Annona muricata Linn.), and Eucalyptus (Melaleuca cajuputi) oil have the potential to serve as natural insecticides due to their active ingredient content in the form of flavonoids, tannins, alkaloids and other bioactive compounds. This study aimed to evaluate the potency of ethanol extracts of betel leaf or soursop leaf in combination with cajeput oil in inducing mortality in C. lectularius. A true experimental design was employed using a post-test only with control group design, which included a positive control (2% bifenthrin), a negative control (distilled water), and 10 treatment groups with combinations of betel leaf or soursop leaf extracts with Eucalyptus oil in ratios of 1:1, 1:2, 2:1, 1:3, and 3:1. Each group consisted of 10 bed bugs, with three replications (totaling 360 bed bugs). Mortality was observed every five minutes over one hour and analysed using the Friedman test. The results indicated significant differences in the potential of the combinations of ethanol extracts and Eucalyptus oil. Probit analysis was used to determine LC₅₀ and LT₅₀ values. The LC₅₀ for the betel leaf and Eucalyptus oil combination was 1.302%, with an LT₅₀ of 0.976 minutes (ratio 1:1). For the soursop leaf and Eucalyptus oil combination, the LC₅₀ was 2.229%, and the LT₅₀ was 0.792 minutes (ratio 1:2). The fastest mortality was observed at five minutes in the combination of soursop leaf and Eucalyptus oil at a 3:1 ratio.